2023
DOI: 10.1002/alr.23204
|View full text |Cite
|
Sign up to set email alerts
|

Recurrence patterns among patients with sinonasal mucosal melanoma: A multi‐institutional study

Abstract: ObjectiveTo evaluate recurrence patterns and survival after recurrence among patients with sinonasal mucosal melanoma (SNMM).MethodsThis was a multi‐institutional retrospective review from seven U.S. institutions of patients with SNMM from 1991 to 2022. Recurrence was categorized as local, regional, distant, or multifocal. Kaplan‐Meier tests were used to evaluate disease‐free survival (DFS), overall survival (OS), and post‐recurrence survival (PRS) reported with standard errors (SE) and log‐rank testing used f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 20 publications
0
0
0
Order By: Relevance
“…Among patients with distant recurrence, immunotherapy was associated with improved 12-month postrecurrence survival (immunotherapy: 61.7% vs no immunotherapy: 33.3%, P = .02). 65 Sayed et al compared 17 SNMM patients with Ipilimumab immunotherapy treatment to 55 patients without and reported 3-year OS for patients with immunotherapy was 51% while the 3-year OS for patients without immunotherapy was 52% (95% CI: −29% to 32%). 51 Although Sayed et al reported no change in survival, they argued that immunotherapy was still benefiting survival because immunotherapy was only given to patients with metastatic and/or recurrent disease.…”
Section: Adjuvant and Salvage Immunotherapy Outcomes And Response Ratementioning
confidence: 99%
“…Among patients with distant recurrence, immunotherapy was associated with improved 12-month postrecurrence survival (immunotherapy: 61.7% vs no immunotherapy: 33.3%, P = .02). 65 Sayed et al compared 17 SNMM patients with Ipilimumab immunotherapy treatment to 55 patients without and reported 3-year OS for patients with immunotherapy was 51% while the 3-year OS for patients without immunotherapy was 52% (95% CI: −29% to 32%). 51 Although Sayed et al reported no change in survival, they argued that immunotherapy was still benefiting survival because immunotherapy was only given to patients with metastatic and/or recurrent disease.…”
Section: Adjuvant and Salvage Immunotherapy Outcomes And Response Ratementioning
confidence: 99%